Probing the formation of isolated cyclo-FF peptide clusters by far-infrared action spectroscopy. Issue 37 (21st September 2021) - Bakels, Sjors; Stroganova, Iuliia; Rijs, Anouk M.
Abstract : Rigid cyclo-FF peptide aggregates have been studied under isolated conditions using a molecular beam-laser desorption setup. Far-IR action spectroscopy provided highly diagnostic spectra, allowing the assignment of various ladder-like conformations. Abstract : Small cyclic peptides containing phenylalanine residues are prone to aggregate in the gas phase into highly hydrophobic chains. A combination of laser desorption, mass spectrometry and conformational selective IR-UV action spectroscopy allows us to obtain detailed structural insights into the formation processes of the cyclic l -phenylalanyl-l -phenylalanine dipeptide (named cyclo-FF) aggregates. The rigid properties of cyclo-FF result in highly resolved IR spectra for the smaller clusters ( n ≤ 3) and corresponding conformational assignments. For the higher order clusters ( n > 3) the spectra are less resolved, however the observed ratios, peak positions and trends in IR shifts are key to make predictions on their structural details. Whereas the mid-IR spectral region between 1000–1800 cm −1 turns out to be undiagnostic for these small aggregates and the 3 μm region only for specific calculated structures, the far-IR contains valuable information that allows for clear assignments.